2020
DOI: 10.3389/fonc.2020.01274
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase Type 5 Inhibitors Synergize Vincristine in Killing Castration-Resistant Prostate Cancer Through Amplifying Mitotic Arrest Signaling

Abstract: Combination therapies that display cancer-killing activities through either coexistent targeting of several cellular factors or more efficient suppression of a specific pathway are generally used in cancer treatment. Sildenafil, a specific phosphodiesterase type 5 (PDE5) inhibitor, has been suggested to display both cardioprotective and neuroprotective activities that provide a rationale for the combination with vincristine on the treatment against castration-resistant prostate cancer (CRPC). In the present wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Further exploration in the molecular pathways responsible for this phenomenon identified a lower percentage of Ki67-positive nuclei and a higher frequency of cleaved caspase-3 positive cells relative to groups treated with monotherapy, thus promoting apoptosis and tumor regression [50]. Likewise, Hsu, J.-L. et al reported the synergestic effects between vincristine and sildenafil in PC-3-derived cancer xenografts in nude mice demonstrating a decrease in tumor weight relative to the single chemotherapeutic agent [46]. 4.…”
Section: In Vitro and In Vivo Applications Of Sildenafil In Cancer Treatmentmentioning
confidence: 98%
See 2 more Smart Citations
“…Further exploration in the molecular pathways responsible for this phenomenon identified a lower percentage of Ki67-positive nuclei and a higher frequency of cleaved caspase-3 positive cells relative to groups treated with monotherapy, thus promoting apoptosis and tumor regression [50]. Likewise, Hsu, J.-L. et al reported the synergestic effects between vincristine and sildenafil in PC-3-derived cancer xenografts in nude mice demonstrating a decrease in tumor weight relative to the single chemotherapeutic agent [46]. 4.…”
Section: In Vitro and In Vivo Applications Of Sildenafil In Cancer Treatmentmentioning
confidence: 98%
“…The effect of co-administration of vincristine and sildenafil on PC-3 and DU145 human prostate cancer cell lines showed that a significant increase in vincristine-induced mitotic arrest and mitotic index [46]. The probability of cells being held in metaphase were dramatically increased in presence of sildenafil.…”
Section: In Vitro and In Vivo Applications Of Sildenafil In Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of coadministration of vincristine and sildenafil on PC-3 and DU145 human prostate cancer cell lines showed that a significant increase in vincristine-induced mitotic arrest and mitotic index [ 46 ]. The probability of cells being held in metaphase was dramatically increased in presence of sildenafil.…”
Section: In Vitro and In Vivo Applications Of Sildenafil In Cancer Treatmentmentioning
confidence: 99%
“…Combining vincristine with sildenafil (10-25µM) is an approach to achieving greater efficacy at lower doses to reduce toxicity. Sildenafil has been shown to synergistically amplify the action of vincristine on tumor cells both in vitro (PC-3 and DU-145 cell lines) and in vivo (65).…”
Section: Prostate Cancermentioning
confidence: 99%